The world's religions. - Clarke, Peter B. (Peter Bernard); Sutherland, Stewart R. (Routledge, 1991)
Examines the `primitive' (traditional) non -mainstream religion and also 20th century sects such as the Moonies and Scientology. Looks at the `nature' of religion - the general philosophical issues. Written by international specialists.
"First published in 1988 as part of The world's religions"--Title page verso
Keywords: Religion.; Religions.; Cults.; Religion; religion (discipline); religions (belief systems, cultures); RELIGION -- Comparative Religion.; RELIGION -- Reference.; Cults; Religions; Aufsatzsammlung; Religionsvergleich; Godsdienst.; Godsdiensten.